Dominican Republic : Second and Third Reviews Under the Stand-By Arrangement and Request for Waivers of Applicability-Staff Report; Staff Supplement; Informational Annex; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, against the background of deteriorating external conditions owing to the global crisis, a 28-month Stand-By Arrangement (SBA) for the Dominican Republic is reviewed. The objective is to limit the procyclicality of policies in the short term. The macroeconomic situation has improved significantly. All performance criteria and structural benchmarks were observed. IMF staff supports completion of the second and third SBA reviews and the targets proposed for 2011 in view of the positive macroeconomic performance. Additional measures have been introduced to meet program targets.